Group Cognitive–Behavioral Therapy in a Sample of Dutch Intimate Partner Violence Perpetrators: Development of a Coding Manual for Therapist Interventions. Issue 4 (2nd October 2022) - van Tilburg, Carola A.; van Dam, Arno; de Wolf-Jacobs, Edith; de Ruiter, Corine; Smeets, Tom
ABSTRACT: This qualitative study investigated which types of interventions are made by group therapists during group cognitive–behavioral therapy (GCBT) with individuals who have perpetrated intimate partner violence (IPV) in the "Not 'Losing It' Anymore"(NLIA) outpatient programs across the Netherlands. Audio recordings of group sessions (N = 60) facilitated by 13 co-therapist teams across 25 different groups were analyzed using the general inductive approach. Fifteen distinct therapist interventions were identified, categorized, and described using examples from the data. Two categories of interventions could be distinguished: CBT interventions and process-oriented interventions. In future research the coding manual can be tested for interrater reliability and might be used in research on the effectiveness of GCBT therapist interventions.